Examining selective exposure and disaster information literacy among Generation Z Instagram users - Lavigne, Franck; Rizal, Edwin; Hadian, Mohamad Sapari Dwi (Jurnal Informatio, 2026)
Background: As a disaster-prone nation, Indonesia requires robust disaster information literacy. Generation Z, as active social media users, demonstrates distinct patterns of selective exposure to earthquake information on Instagram, influenced by psychological needs, message relevance, and social context.Purpose: This study aims to analyze the psychological factors, message features, and social contexts that influence Generation Z’s selective exposure to local earthquake information on Instagram within the framework of disaster information literacy.Methods: Utilizing a qualitative case study approach centered on the Sumedang earthquake (June 31, 2025–November 5, 2025), this research employed in-depth interviews with six informants, focus group discussions, and visual discourse analysis of 45 posts from local Instagram accounts (@radarsumedang, @inimahsumedang, @tahuekspress, and @sumedangekspresnews). Interviews lasted 45-60 minutes each and were analyzed using NVivo 12 software.Results: Selective exposure is driven by trust, affective needs, and practical motivations. Message features—specifically Instagram Stories for rapid updates, feed posts for in-depth narratives, and infographics for clarity—play a critical role. Furthermore, the social context, including peer recommendations, comment-based verification, and the editorial strategies of local media, significantly shapes engagement. Generation Z demonstrates situational, heterogeneous, and dialogic interaction patterns with disaster information, balancing cognitive needs for accuracy with affective needs for emotional reassurance.Conclusions: Disaster information literacy for Generation Z requires a hybrid strategy that integrates speed, accuracy, empathy, and interactivity to strengthen community preparedness and resilience. This study extends Selective Exposure Theory by identifying "emotional certainty" as a novel motivation, enriches Uses and Gratifications Theory through situational gratifications, and advances Situational Crisis Communication Theory by emphasizing collective social validation in social media-based disaster contexts.